Characterization and Genomic Analysis of Two Novel Psychrotolerant Acidithiobacillus Ferrooxidans Strains from Polar and Subpolar Environments - Levican-Jaque, G; Muñoz-Villagran, C; Grossolli-Gálvez, J; Acevedo-Arbunic, J (Frontiers Media S.A., 2022)
The bioleaching process is carried out by aerobic acidophilic iron-oxidizing bacteria that are mainly mesophilic or moderately thermophilic. However, many mining sites are located in areas where the mean temperature is lower than the optimal growth temperature of these microorganisms. In this work, we report the obtaining and characterization of two psychrotolerant bioleaching bacterial strains from low-temperature sites that included an abandoned mine site in Chilean Patagonia (PG05) and an acid rock drainage in Marian Cove, King George Island in Antarctic (MC2.2). The PG05 and MC2.2 strains showed significant iron-oxidation activity and grew optimally at 20°C. Genome sequence analyses showed chromosomes of 2.76 and 2.84 Mbp for PG05 and MC2.2, respectively, and an average nucleotide identity estimation indicated that both strains clustered with the acidophilic iron-oxidizing bacterium Acidithiobacillus ferrooxidans. The Patagonian PG05 strain had a high content of genes coding for tolerance to metals such as lead, zinc, and copper. Concordantly, electron microscopy revealed the intracellular presence of polyphosphate-like granules, likely involved in tolerance to metals and other stress conditions. The Antarctic MC2.2 strain showed a high dosage of genes for mercury resistance and low temperature adaptation. This report of cold-adapted cultures of the At. ferrooxidans species opens novel perspectives to satisfy the current challenges of the metal bioleaching industry. Copyright © 2022 Muñoz-Villagrán, Grossolli-Gálvez, Acevedo-Arbunic, Valenzuela, Ferrer, Díez and Levicán.